A Review of The Role of Political Buzzers in Indonesia Using The Hadith Ahkam Approach - Haeruddin; Abdul Rahman Sakka; Andi Muh. Taqiyuddin BN; Ahmad Arief; Samsidar Jamaluddin (Pusat Studi Hukum Islam (PSHI) YPI Shafal 'Ulum Al-Aziziyah, 2025)
This study discusses the shift in the role of buzzers towards the political arena in Indonesia, causing confusion among the online and offline public. This is likely due to the fact that regulations regarding political buzzers, in particular, are still vague. For example, the ITE Law can ensnare buzzers or those who threaten their existence. Political buzzers often raise identity issues, such as the personalities of candidates and messages with religious themes. They have the ability to shape public perception of certain candidates. The concept of buzzers, which previously had positive connotations, has shifted to become negative. This is because they can divide society by spreading hoaxes and hate speech. This research is qualitative, using library research as the type of research. The data collection method used is literature study, with a hadith ahkam approach. The findings reveal that the term ‘buzzer’ indirectly refers to practices such as gossip, slander, and propaganda in the context of hadith ahkam. These practices are fundamentally prohibited under Islamic law and positive law. However, within the framework of positive law, there are still loopholes that allow political buzzers to evade the legal consequences of their actions.